1451. Predictive Values of Methicillin-Resistant Staphylococcus aureus (MRSA) Nasal Swab PCR Assay for MRSA Pneumonia. (26th November 2018) - Chou, Man Ting; Eskandarian, Romic; Jung, Hemi; Pineda, Ross; Lee, Su; Kawaguchi, Keitaro
Abstract: Background: The Center for Disease Control (CDC) reports that methicillin-resistant Staphylococcus aureus (MRSA) has being linked to over 80, 000 severe infections and 11, 000 deaths per year. Due to this concern, patients are commonly and overly started on empiric MRSA-targeted antimicrobial agents. Antimicrobial stewardship encourages the rapid de-escalation of therapy to minimize the overuse of antibiotics and reduce resistance. In pneumonia, respiratory cultures are used to confirm organism(s) which may take days to result. Recent emerging literature suggests that the use of MRSA nasal swab PCR assay as a predictive diagnostic tool for MRSA pneumonia to shorten the duration of empiric therapy. The primary objective of this study was to assess both the positive and negative predicative values of the MRSA nasal swab for MRSA pneumonia. Methods: We conducted a single-centered, retrospective chart review of all patients admitted from February 2017 to 2018 with a confirmed diagnosis of pneumonia. Patients who were screened for MRSA nares and had a respiratory culture within 48 hours of the screening were included in this study. Patients who failed to meet these criteria, they were excluded from the study. This study has been exempt from the Institutional Review Board (IRB). Results: One hundred seventy-four patients met the inclusion criteria, 30 with positive MRSA nares and 144 with negative MRSA nares. No statistical differences were found between baseline characteristics between the two groups. The positive predictive value of the MRSA nasal swab for MRSA pneumonia was 0.3 and its negative predictive value was 0.97. The sensitivity was 64% and the specificity was 87%. Conclusion: MRSA nasal swab has a high negative predictive value to rule out MRSA pneumonia and reduces time to discontinuation of empiric MRSA-targeted antimicrobial agents. The positive predictive value was low and should not be used as a sole factor to initiate antimicrobial therapy. Disclosures: All authors: No reported disclosures.